Craqueamento de cicloexano sobre zeólitas ácidas : atividade, seletividade e influência da presença de mesoporosidade - Gonçalves, Alexandre Amormino dos Santos (2012)
The need to develop a catalyst capable of processing heavy oil fractions, which is extracted from deeper wells, is essential. This concern has become more remarkable with the discovery of new oil fields in Brazil. This expectation, which will sustain the country's independence concerning to the production of oil and its derivatives, has led to profound changes in the scientific and technological strategies of Petrobras, in order to provide the necessary knowledge for the processing and production of Petroleum derivatives, attending the various quality and environmental constraints, as well as provide raw material for the growing demand of the petrochemical industry. In this complex context, the study of catalysts for obtaining light hydrocarbons by cracking of heavy fractions of petroleum became an important strategy. The zeolites used in this process, in despite of be very actives, have restrictions regarding to internal diffusion of bulky molecules, which must be overcome. The present research is inserted in this background. The studies were directed in a first step to check the activity and selectivity of acid zeolites in the cracking of cyclohexane, used as a model molecule. The evaluation of H-ZSM-5, H-mordenite, H-Ferrierite, H-Beta and USY, showed that the activity was greatly influenced by the number of external sites and the great potential of the H-Beta zeolite to be applied in naphthenic cracking, because it showed high activity and a better yield to light olefins than USY zeolite, used commercially. The H-ZSM- 5 zeolite confirmed their high potential as catalyst for this process. The cracking of cyclohexane on the H-zeolites also showed the influence of the external sites. Expecting to overcome the diffusional limitations in microporous commented above, in a second step, the study was focused on the preparation of solids containing micro and mesoporous. The method of nanoclusters ZSM-5 zeolite aggregation in a mesostructure matrix was used, resulting in a solid composed by a segregated material of MCM-41 and ZSM-5, but with high catalytic potential. In the materials characterization were used X-ray diffraction (XRD) at low and wide angles, scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDS), temperature-programmed desorption of NH3 (TPD-NH3), N2 Physisorption and nuclear magnetic resonance of Al27 (NMR Al27).